2018
DOI: 10.1371/journal.pbio.2003805
|View full text |Cite
|
Sign up to set email alerts
|

Serial representation of items during working memory maintenance at letter-selective cortical sites

Abstract: A key component of working memory is the ability to remember multiple items simultaneously. To understand how the human brain maintains multiple items in memory, we examined direct brain recordings of neural oscillations from neurosurgical patients as they performed a working memory task. We analyzed the data to identify the neural representations of individual memory items by identifying recording sites with broadband gamma activity that varied according to the identity of the letter a subject viewed. Next, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 90 publications
(124 reference statements)
11
88
0
Order By: Relevance
“…PAC has been suggested to reflect the regulation of sensory information processing achieved in higher frequencies through excitability fluctuations imposed by slower oscillations [9,10,34,36,37,42]. These results, despite methodological differences, are similar to previous findings that have reported PAC in the rat hippocampus [46,47], non-human primates [82,83], and in human intracranial EEG [48][49][50][51]60] and EEG and MEG recordings [54][55][56][84][85][86]. In contrast to PAC, inter-areal CFS connected the phase of  oscillations with the phases of and oscillations only with small frequency ratios (1:2 and 1:3).…”
Section: Large-scale Cfc Network Characterize Human Resting-state Brsupporting
confidence: 88%
See 1 more Smart Citation
“…PAC has been suggested to reflect the regulation of sensory information processing achieved in higher frequencies through excitability fluctuations imposed by slower oscillations [9,10,34,36,37,42]. These results, despite methodological differences, are similar to previous findings that have reported PAC in the rat hippocampus [46,47], non-human primates [82,83], and in human intracranial EEG [48][49][50][51]60] and EEG and MEG recordings [54][55][56][84][85][86]. In contrast to PAC, inter-areal CFS connected the phase of  oscillations with the phases of and oscillations only with small frequency ratios (1:2 and 1:3).…”
Section: Large-scale Cfc Network Characterize Human Resting-state Brsupporting
confidence: 88%
“…During task performance, PAC has been suggested to reflect the regulation of sensory information processing in  and -frequencies by excitability fluctuations imposed by  and  oscillations [9,10,34,36,37,42]. A large number of studies have identified local PAC, i.e., PAC observed between different frequency bands of the same signal, between the phases of slower oscillations in delta (13 Hz, theta (37Hz) and  frequency bands and the amplitude of  oscillations in local field potentials (LFPs) in rats [43][44][45][46][47] and in human intracranial EEG [48][49][50][51] and MEG data [52][53][54][55][56]. Such local PAC has cortex-wide spatial modes akin to RSNs [53].…”
Section: Introductionmentioning
confidence: 99%
“…During task performance, PAC has been suggested to reflect the regulation of sensory information processing in β-and γ-frequencies by excitability fluctuations imposed by θ and α oscillations [9,10,34,36,37,42]. A large number of studies have identified local PAC, i.e., PAC observed between different frequency bands of the same signal, between the phases of slower oscillations in delta-(δ, 1-3 Hz), theta-(θ, 3-7 Hz), and α-frequency bands and the amplitude of γ oscillations in local field potentials (LFPs) in rats [43][44][45][46][47] and in human intracranial EEG [48][49][50][51] and MEG data [52][53][54][55][56]. Such local PAC has cortex-wide spatial modes akin to RSNs [53].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from alpha activity, oscillatory activity in the theta (5-7 Hz) and gamma (60-80 Hz) frequency bands have also been linked to working memory. It has been proposed that theta-band oscillations underlie the organization of sequentially ordered working memory items, whereas gamma-band oscillations are thought to contribute to the maintenance of working memory information [24,[26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%